2017
DOI: 10.2217/fon-2017-0166
|View full text |Cite
|
Sign up to set email alerts
|

Postsorafenib systemic treatments for hepatocellular carcinoma: questions and opportunities after the regorafenib trial

Abstract: The search for systemic therapies for hepatocellular carcinoma has been characterized by difficulties and failures. Despite recent progresses, many issues are still to be settled. In particular, the development of drugs inhibiting different neoplastic pathways remains a priority for patients intolerant or resistant to antiangiogenic drugs. This task may be daunting, as previous failures extensively demonstrated. We aimed to identify the future perspective of postsorafenib trials analyzing the strengths and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Tailored treatment according to the individual HCC genetic profile could provide therapeutic choices beyond standard sorafenib regimen for liver cancers. 160,161 From this perspective, as galunisertib is not similarly effective in all patients, several studies have been aimed at identifying new potential diagnostics biomarkers for patient stratification. In one study, next-generation sequencing-based massive analysis of cDNA ends was used to investigate the transcriptome of an invasive HCC cell line responses to TGF-β1 and galunisertib.…”
Section: Intracellular Level: Signal Transduction Blockade By Recep-mentioning
confidence: 99%
“…Tailored treatment according to the individual HCC genetic profile could provide therapeutic choices beyond standard sorafenib regimen for liver cancers. 160,161 From this perspective, as galunisertib is not similarly effective in all patients, several studies have been aimed at identifying new potential diagnostics biomarkers for patient stratification. In one study, next-generation sequencing-based massive analysis of cDNA ends was used to investigate the transcriptome of an invasive HCC cell line responses to TGF-β1 and galunisertib.…”
Section: Intracellular Level: Signal Transduction Blockade By Recep-mentioning
confidence: 99%
“…Overall, the results of the CheckMate-459 and KEYNOTE-240 trials suggested that: (1) The design of clinical trials remains a critical point in HCC trials, as seemingly minor pitfalls can determine the failure of the trial [ 21 ]; (2) the safety profile of nivolumab and pembrolizumab was excellent, with an impact on the quality of life significantly lower than that of sorafenib in the CheckMate-459 study [ 11 ]; (3) an objective response could be achieved in 15–20% of cases, leading to a long-term survival in responding patients [ 11 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a first point, we demonstrated an improved OS in comparison with matched patients treated with BSC alone. The potential mechanisms of actions of MC have been previously illustrated 26 and include: inhibition of tumor angiogenesis, reduction of the therapeutic resistance of the tumor, and activation of the adaptive and innate immune response 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%